PENILAIAN TERHADAP IKLIM INVESTASI USAHA PENGOLAHAN KELAPA SAWIT DI KABUPATEN BENGKULU SELATAN - Adwirman Adwirman; Muhammad Firdaus; Idqan Fahmi (School of Business, Bogor Agricultural University (SB-IPB), 2012)
ABSTRACTThe purposes of this study were (1) to identify factors that considered important by investors in making investment decisions in the oil palm agribusiness and in the performance of South Bengkulu Regency Officials in providing a supporting investment climate, (2) to determine the Regional Official’s level of compatibility and value of performance index towards factors that influencing investment, (3) to determine the difference in perception toward the (what) variables, between investors and South Bengkulu Regency Government, (4) to formulate strategies which can be used by South Bengkulu Regency to attract investors. The methods used to collect data were observation, questionnaire-based interview, and in-depth interview. The techniques used to analyze data were descriptive analysis, importance-performance analysis, Value of Performance Index, and Mann Whitney’s independent sample test. A comprehensive analysis of the output of the three methods had concluded that South Bengkulu Regency need to concern about 24 variables and its managerial implications in order to attract investors on PKS or CPO factories. Keywords: oil palm agribusiness, South Bengkulu, IPA matrix, CSI, mann whitneyABSTRAKTujuan dari penelitian ini adalah (1) mengidentifikasi faktor-faktor yang dianggap penting oleh investor untuk membuat keputusan investasi pabrik crude palm oil dan kinerja Pemerintah Kabupaten Bengkulu Selatan dalam menyediakan iklim investasi, (2) menentukan tingkat kompatibilitas dan nilai indeks kinerja Pemerintah Daerah (Pemda) terhadap faktor yang memengaruhi investasi (3) menentukan perbedaan persepsi terhadap variabel, antara investor dan Pemerintah Kabupaten Bengkulu Selatan. (4) merumuskan strategi Pemerintah Kabupaten Bengkulu Selatan untuk menarik investor. Metode pengumpulan data mengunakan observation, questionnaire-based interview, dan in-depth interview. Analisis data yang digunakan berupa metode importance-performance analysis, nilai indeks kinerja, dan uji Mann Whitney sampel independen. Hasil analisis dari tiga metode tersebut menyimpulkan bahwa Kabupaten Bengkulu Selatan perlu memperbaiki sekitar 24 variabel dan melaksanakan strategi dalam rangka menarik investors pabrik CPO atau PKS. Kata kunci: kelapa sawit, Bengkulu Selatan, IPA matrix, CSI, mann whitney